Mental health symptoms are related to mothers' use of controlling and responsive child feeding practices: A replication and extension study. (1st April 2020) - Haycraft, Emma
Abstract: Parents have an important role in feeding their children. Parents' child feeding practices can be influenced by numerous factors. The presence of mental health symptoms can be associated with more controlling, less sensitive parent-child feeding interactions. However, it is not known whether mental health symptoms are related to parents' use of responsive, more autonomy supportive feeding practices which are important for promoting children's healthy eating habits. This study therefore aimed to examine the relationships between mental health symptoms and the use of controlling and responsive child feeding practices. A community sample of 415 UK mothers with a child age 2–4 years took part. They completed self-report measures of their levels of anxiety, depression and disordered eating behaviours as well as a comprehensive measure of their child feeding practices. The presence of mental health symptoms was significantly associated with greater self-reported use of controlling feeding practices, such as more restriction for weight control and using food as a reward. Maternal symptoms of anxiety and depression were related to lower use of modelling and monitoring but to giving children more control around food. Mothers' restrained and external eating behaviours were associated with greater use of several responsive feeding practices, including encouraging balance and variety, involvement, and teaching about nutrition. Together, these findings highlight the broad impact that mental health symptoms can have on mothers' controlling and responsive child feeding interactions. Interventions to support families to promote healthy child eating habits need to be aware of the role of even fairly mild, non-clinical levels of mental health symptoms on maternal sensitivity and involvement in feeding their children.